The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/brain/awt131
|View full text |Cite
|
Sign up to set email alerts
|

Boosting chaperone-mediated autophagy in vivo mitigates α-synuclein-induced neurodegeneration

Abstract: α-Synuclein levels are critical to Parkinson's disease pathogenesis. Wild-type α-synuclein is degraded partly by chaperone-mediated autophagy, and aberrant α-synuclein may act as an inhibitor of the pathway. To address whether the induction of chaperone-mediated autophagy may represent a potential therapy against α-synuclein-induced neurotoxicity, we overexpressed lysosomal-associated membrane protein 2a, the rate-limiting step of chaperone-mediated autophagy, in human neuroblastoma SH-SY5Y cells, rat primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
156
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(159 citation statements)
references
References 51 publications
3
156
0
Order By: Relevance
“…In summary, the results of this research confirm a previously little-known cross-talk between macroautophagy and CMA in lymphoma Raji cells facing different stressors, and these findings must be helpful to understanding the characteristics, compensatory mechanisms and answer mode of different autophagic pathways in cancer cells, which may be very important and promising to the development of interventions targeting regulate one form of autophagy for potential targeting therapeutic purposes in human diseases, such as cancer or neurodegenerative disorders (Kon et al, 2011;Saha, 2012;Xilouri et al, 2013). Up-regulation of one autophagic pathways after the failure of another particular form of autophagy can be the basis for future therapeutic interventions to preserve normal cellular function in these pathologies.…”
Section: Discussionsupporting
confidence: 73%
“…In summary, the results of this research confirm a previously little-known cross-talk between macroautophagy and CMA in lymphoma Raji cells facing different stressors, and these findings must be helpful to understanding the characteristics, compensatory mechanisms and answer mode of different autophagic pathways in cancer cells, which may be very important and promising to the development of interventions targeting regulate one form of autophagy for potential targeting therapeutic purposes in human diseases, such as cancer or neurodegenerative disorders (Kon et al, 2011;Saha, 2012;Xilouri et al, 2013). Up-regulation of one autophagic pathways after the failure of another particular form of autophagy can be the basis for future therapeutic interventions to preserve normal cellular function in these pathologies.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, a sequence variation in the promoter region of LAMP-2 identified recently in a PD patient [61], opens up the possibility that alterations in CMA components may be behind some forms of PD. The fact that both chemical [31] and genetic [62] upregulation of CMA have been shown to be capable of alleviating cellular toxicity associated with pathogenic forms of α-synuclein supports that the changes in CMA observed in PD are not a mere consequence of the disease, but that rather they contribute to pathogenesis.…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 87%
“…The growing number of connections between CMA and human diseases has generated interest in modulating CMA activity for therapeutic purposes. Genetic manipulation to enhance CMA has proved useful in mitigating mutant α-synuclein-induced neurodegeneration in mouse models of PD [62]. Similarly, experimental upregulation of CMA also attenuates the toxicity associated with HD in brain slice cultures [18] and interventions that enhance targeting of the HD toxic protein to CMA have also succeeded in slowing down neurodegeneration in HD mouse models [85].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that RNA-interference targeting LAMP2A results in significant accumulation of SNCA in cultured neurons, 17 whereas overexpression of LAMP2A in cell culture models and in dopaminergic neurons of the substantia nigra pars compacta (SNpc) is able to fully rescue neurotoxicity associated with elevated SNCA protein burden. 25 However, the importance of proper CMA function in the living brain and the consequences of malfunction of this pathway in brain physiology remain unknown.…”
Section: Introductionmentioning
confidence: 99%